Nitrogen-doped bagasse carbon spheres/graphene composite for high-performance supercapacitors. (February 2021) - Ye, Weijie; Cai, Jihai; Yu, Fanzhe; Li, Xiaoyun; Wang, Xiaoying
Abstract: Carbon spheres have emerged as a promising material in energy storage, but preparing carbon spheres from raw biomass in a cost-effective way still remains as a great challenge. Here, for the first time, we directly transformed bagasse to nitrogen-doped carbon sphere through hydrothermal carbonization. Before carbonization, bagasse and graphene oxide was fully dissolved in NaOH/urea aqueous system. In the process of hydrothermal carbonization, graphene oxide acted as template and accelerant, and urea was acted as nitrogen source. The diameter of the prepared carbon spheres was about 200 nm, which were distributed on the graphene sheets and acted as spacer to prevent aggregation of graphene sheets. The nitrogen-doped bagasse-based carbon spheres/reduced graphene oxide composite exhibited 3D interconnected structures with high electrical conductivity, large specific surface areas, and active nitrogen-doped sites. Applied as electrode material for supercapacitor, the composite showed a higher specific capacitance, rate capability and better cycling stability compared to some traditional carbon spheres, active carbon and reduced graphene oxide. The specific capacitance is 226.8 F g −1 at the current density of 0.5 A g −1, which still retains 83.9% after 10, 000 cycles. After 10, 000 cycles, the composite maintains 83.9% of the initial capacitance. Furthermore, the possible formation mechanism of nitrogen-doped bagasse-based carbon spheres/reduced graphene oxide composite was discussed. This study achieved full solubility of bagasse in NaOH/urea aqueous system, not only providing a promising way to convert lignocellulosic raw biomass into carbon spheres directly, but also proposing an emerging strategy for synthesizing high capacitive and stable biomass-based electrode material. Graphical abstract: Bagasse was transformed to nitrogen-doped carbon spheres and used as supercapacitor electrodes, which is the high-value utilization of renewable resources.Illustration for the preparation of bagasse-based carbon spheres/RGO composite, and application as supercapacitor electrodes. Image 1 Highlights: Carbon sphere was prepared in a direct and cost-effective way. Raw biomass like bagasse was chose as carbon precursor. Bagasse was firstly dissolved in NaOH/urea solution to form homogenous mixture. Graphene oxide was used as template and accelerant. Show better performance than those of many reported carbon spheres and porous carbon materials.